Al-Radd al-jamil : a fitting refutation of the divinity of Jesus - Beaumont, Ivor Mark; Elkaisy-Friemuth, Maha (Leiden ; Boston : Brill, 2016)
Al-Radd al-jamil' attributed to al-Ghazali (d. 1111) is the most extensive and detailed refutation of the divinity of Jesus by a Muslim author in the classical period of Islam. Since the discovery of the manuscript in the 1930's scholars have debated whether the great Muslim theologian al-Ghazali was really the author. This is a new critical edition of the Arabic text and the first complete English translation. The introduction situates this work in the history of Muslim anti-Christian polemical writing. Mark Beaumont and Maha El Kaisy-Friemuth argue that this refutation comes from an admirer of al-Ghazali who sought to advance some of his key ideas for an Egyptian audience.
Includes bibliographical references (pages 195-200) and index.
English and Arabic.
Sumbangan Siti Hawa Majid (2018).
Keywords: Jesus Christ -- Islamic interpretations -- Early works to 1800.; Bible. -- Islamic interpretations -- Early works to 1800.; Prophecy -- Early works to 1800.; Islam -- Relations -- Christianity -- Early works to 1800.